Canva-Based Digital Platform Supervision at the Assunnah Foundation in Gorontalo - Zulkifly Lasena; Abdul Kadim Masaong; Besse Marhawati (Darul Yasin Al Sys, 2026)
Academic supervision in madrasahs is still commonly conducted through conventional mechanisms, limiting its capacity to provide effective, rapid, systematic, and sustainable feedback for improving teacher professionalism. This study aims to develop a Canva digital platform-based supervision model to improve the effectiveness of teacher coaching and learning quality in madrasahs and schools under the As Sunnah Foundation in Gorontalo Regency, covering needs analysis, model design, implementation, and its impact on teachers’ professional competence. This study was conducted at the As Sunnah Foundation in Gorontalo using a qualitative Research and Development (R&D) design based on the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through observation, interviews, and documentation, and analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. The findings show that Canva Web-based supervision improves the effectiveness and efficiency of academic supervision through easier access, flexible communication, digital documentation, and strengthened learning reflection. The use of Canva also positively affects teachers’ professional competence, openness to feedback, lesson planning quality, use of learning media, and classroom management. In addition, digital supervision helps madrasah principals reduce administrative burdens and support data-driven decision-making. The study concludes that Canva Web-based academic supervision offers a practical digital transformation model for strengthening teacher coaching and improving learning quality in Islamic educational institutions. These findings contribute to educational supervision literature by demonstrating the potential of accessible digital platforms to support systematic, reflective, and data-informed professional development.